Pengaruh Financial Socialization dan Literasi Keuangan Terhadap Perilaku Konsumtif - Ismi Untari, (Seminar Nasional Manajemen, 2026)
Consumer behavior among university students is a phenomenon influenced by various factors, including the process of financial socialization and levels of financial literacy. This study aims to analyze the influence of financial socialization and financial literacy on the consumer behavior of students at Surabaya State University during the 2024/2025 academic year. The study employs a quantitative approach using an associative method. Primary data were collected through a questionnaire using a Likert scale and analyzed using SPSS 25 through validity, reliability, classical assumptions, multiple linear regression, and hypothesis testing. The results indicate that financial socialization has a positive and significant influence on students' consumer behavior, while financial literacy has a negative and significant influence on consumer behavior. These findings indicate that the more intensive the financial education received by students, the higher their tendency toward consumptive behavior, and that a high level of financial literacy is capable of controlling such behavior. This study recommends enhancing financial education from families, educational institutions, and the media to foster wise consumption behavior.